Pertanggung Jawaban Pidana Perkosaan Ayah Terhadap Anak Kandung Di Pengadilan Negeri Kelas 1 Kupang (Putusan Nomor 113/PID.SUS/2021/ PN KPG ) - Fransiskus Varan Amaina; Orpa G. Manuain; Rosalind Angel Fanggi (Law Faculty, Nusa Cendana University, 2026)
Criminal liability for the perpetrator of the crime of rape committed by a father against his biological child is determined based on the fulfillment of the elements of actus reus (act) and mens rea (evil intent). Therefore, the author conducted this study with the following objectives: 1) To find out and analyze the punishment of the father as the perpetrator of the crime of rape against his biological child based on Decision Number 113/Pid.Sus/2021/PN Kpg. 2) To find out and analyze the Judge's Decision Number 113/Pid.Sus/2021/PN Kpg in providing justice to the victim. This study uses a normative legal research type by examining laws and court decisions. The sources of legal materials used are primary legal materials, secondary legal materials and tertiary legal materials which are then analyzed descriptively qualitatively. The results of the study show that although the perpetrator was legally proven to have committed the crime of rape against his child, the panel of judges did not impose an additional sentence of one third of the main sentence which should have increased the sentence because the perpetrator was the biological father of the victim's child. In fact, the actus reus element has been fulfilled through the crime of rape committed by force, and mens rea has also been seen from the perpetrator's intention and knowledge of the victim's status as his biological child. The absence of an additional one-third sentence reflects that justice for child victims has not been fully fulfilled in providing protection for child victims.